THE EFFECT OF INTELLECTUAL CAPITAL AND ISLAMICITY PERFORMANCE INDEX TO THE PERFORMANCE OF ISLAMIC BANK IN INDONESIA 2010-2014 PERIODS - Dewanata, Pandu; Hamidah, Hamidah; Ahmad, Gatot Nazir (Fakultas Ekonomi, Universitas Negeri Jakarta, 2016)
The purpose of this research is to know the influence of intellectual capital and islamicity performance index by proxy is profit-sharing ratio, zakat performance ratio, and equitable distribution ratio on performance of Islamic bank in Indonesia in the period 2010-2014. The data used in this research is financial statement of 11 Islamic bank in Indonesia 2010-2014 periods. Regression model using panel data with Fixed Effect Model. The result of this research is intellectual capital and zakat performance ratio has significant and positif impact on ROA, while equitable distribution ratio has not significant impact on ROA, and profit sharing ratio has significant and positif impact on ROA. Keyword: Islamic bank, Performance, Intellectual Capital, Islamicity Performance Index